Three decades of research on washback (1993–2023): a bibliometric study - Qin Xie; Qi Jia (Language Testing in Asia)
Abstract The present research employed bibliometric analyses to systematically examine empirical washback studies published in applied linguistics journals over the past three decades (1993 to 2023). The research identified the distribution of washback scholarships globally and in Asia, the key research themes, and their evolution over time. The primary studies were retrieved from three established databases: Web of Science, Scopus, and ERIC and supplemented by tracking the reference lists of recent publications. Only journal articles of empirical studies written in English were included in the final collection (N = 243). The analysis focused on the distribution of research contexts, most productive journals and authors, prominent research themes, and their evolution over time. The 243 washback studies published in 149 journals were conducted in 40 educational contexts worldwide by 386 researchers. They showed pronounced distribution characteristics, with Asian countries and regions leading this line of research and also exhibiting differences from the research outside of Asia in research foci and methods. The topmost productive and impactful journals, authors, and references of washback research of the past 32 years, alongside the evolving basic, niche, and motor research themes, provide valuable information to understand where we have been and should go.